Do endorser credibility triggers young generations buying decisions? - Rahayu, Ratna Bhanuwati; Pebrianti, Wenny; Purmono, Bintoro Bagus; Juniwati, Juniwati; Jaya, Arman (Enrichment : Journal of Management, 2023)
The development of social media has changed people's interaction patterns. This creates an opportunity for product marketing on social media platforms such as Instagram to increase the product's popularity. One of them is using social media endorsers with solid public influence. This quantitative research aims to determine the impact of endorser credibility on purchasing decisions for Ponds products among the younger generation of Instagram users in Indonesia, which is mediated by attitude toward the brand. This research involved 211 people from various regions in Indonesia who were collected online using Purposive Sampling Techniques through questionnaires. Criteria for samples collected include Ponds product users, Instagram users, and endorser Nanda Arsyinta's content using Ponds products. Data were analyzed using Structural Equation Modeling (SEM) using AMOS 24. The research results stated that endorser credibility positively and significantly affected buying decisions. Meanwhile, endorser credibility positively and significantly affects attitude toward the brand. Attitude toward the brand indirectly influences endorser credibility and purchasing decisions among younger Instagram users in Indonesia. These findings can help businesses determine the right endorser to represent their brand, convey the product message well to consumers, and create sales.